2022
DOI: 10.1080/10717544.2022.2058648
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-coated bovine serum albumin nanoparticles for topical tetrandrine delivery in glaucoma: in vitro and in vivo assessment

Abstract: Glaucoma is one of the leading causes of blindness. Therapies available suffer from several drawbacks including low bioavailability, repeated administration and poor patient compliance with adverse effects thereafter. In this study, bovine serum albumin nanoparticles (BSA-NPs) coated with chitosan(CS) were developed for the topical delivery of tetrandrine (TET) for glaucoma management. Optimized nanoparticles were prepared by desolvation. pH, BSA, CS and cross-linking agent concentrations effects on BSA-NPs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 67 publications
(79 reference statements)
1
12
0
Order By: Relevance
“…The study showed that higher levels of amination can lead to more positive charges on the surface, likely because there are more amino groups [ 44 ]. Similarly, chitosan-coated tetrandrine containing bovine serum albumin nanoparticles were formulated and optimized for the concentration of BSA, chitosan, glutaraldehyde, and pH to achieve the desired physiochemical properties for the effective treatment of ocular glaucoma [ 45 ]. At pH levels above the isoelectric point (pH > 5) of bovine serum albumin, the net charge of a developed nanoparticle is very negative.…”
Section: Different Types Of Chitosan-based Nanomedicine For Ocular Ap...mentioning
confidence: 99%
See 3 more Smart Citations
“…The study showed that higher levels of amination can lead to more positive charges on the surface, likely because there are more amino groups [ 44 ]. Similarly, chitosan-coated tetrandrine containing bovine serum albumin nanoparticles were formulated and optimized for the concentration of BSA, chitosan, glutaraldehyde, and pH to achieve the desired physiochemical properties for the effective treatment of ocular glaucoma [ 45 ]. At pH levels above the isoelectric point (pH > 5) of bovine serum albumin, the net charge of a developed nanoparticle is very negative.…”
Section: Different Types Of Chitosan-based Nanomedicine For Ocular Ap...mentioning
confidence: 99%
“…The developed system helps to improve (4-fold and 1.7-fold) the apparent permeability coefficient compared to tetrandrine suspension and tetrandrine-loaded albumin nanoparticles, respectively. The study also indicated a two-times increase in ocular bioavailability of tetrandrine from developed chitosan-coated albumin nanoparticles compared to tetrandrine suspension and tetrandrine-loaded albumin nanoparticles [ 45 ]. In another study, trimethyl chitosan-coated lipid nanoparticles significantly prolonged the residence of tetrandrine in tears and enhanced ocular absorption as compared to tetrandrine solution [ 62 ].…”
Section: Chitosan-based Nanomedicine For Ocular Application In Glauco...mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Radwan et al [12] prepared bovine serum albumin nanoparticles coated with chitosan by the desolvation method for the topical delivery of tetrandrine for management of glaucoma. The optimized formulation had a size of 237.9 nm and zeta potential of 24 mV and high % EE > 95% with a sustained-release drug profile.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%